The Influence of Promotional Programs on Customer Interest in Using BNI Credit Cards - Mantiri, Anggun Tryuda Ninggrum; Walean, Ronny Hansje (PT Mattawang Mediatama Solution, 2025)
In today's worldwide economy, credit cards have become increasingly popular among consumers. One productthat has been rising quickly recently is the BNI Credit Card. The purpose of this study is to determine whether credit cardpromotions influence consumers' interest in using them as well as whether they can boost consumer satisfaction and brand loyalty. implementing quantitative methods, 302 respondents who already had BNI credit cards were gathered, using the Smart PLS Program and SEM PLS data analysis tools. This study provides a comprehensive description of the factors affecting customer satisfaction, brand loyalty, security measures, service quality, and promotions.